Antimicrobial resistance among important bovine pathogens isolated at the KSU Veterinary Diagnostic Laboratory over two and a half years - Rogers, D.P.; Vorhies, M.W.; Chengappa, M. M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A retrospective study was conducted to determine the prevalence of antimicrobial resistance among six important bacterial pathogens of bovine origin. The study extended from June 1990 through December 1992 and included a review of the microbiology records of bovine submissions to the KSU Veterinary Diagnostic Laboratory. Antimicrobial susceptibility results for Pasteurella haemolytica, Pasteurella multocida, Actinomyces pyogenes, Hemophilus somnus, Escherichia coli, and Salmonella spp. are summarized. Pathogens were recovered primarily from cases of pneumonia and/or diarrhea. Each isolate was tested for susceptibility to 14 different antimicrobial agents. A high prevalence of resistance (>70%) was noticed for respiratory pathogens to sulfachloropyridazine. In addition, Pasteurella spp. were very resistant (>71%) to sulfadimethoxine. Most of the H. somnus isolates showed little resistance (<35%) to 12 of the 14 drugs tested. A. pyogenes isolates were generally susceptible to most antimicrobials except sulfa drugs. As expected, a high prevalence of resistance (>70%) was noticed for enteric pathogens (Salmonella and E. coli) to most of the antimicrobials tested.
Keywords: Beef; Resistance; Disease; Bacteria; Treatment; Cattle